2023
DOI: 10.1186/s40834-023-00236-w
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary care for infertile couples: aetiological diagnoses and conventional treatment outcomes in Kisangani, Democratic Republic of the Congo

Abstract: Background In sub-Saharan Africa, tubal factors are described as the main aetiological factors of infertility. Under these conditions, medically assisted procreation is particularly indicated. However, Assisted Reproductive Technology centres are less available. Thus, infertile couples are quickly oriented towards available alternative conventional treatments. The present study aimed to determine the aetiological factors of infertility, the outcomes of the therapeutic options offered, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Among women experiencing infertility, 78.78% had secondary infertility, while 21.22% had primary infertility. The results of this study are in agreement with those of Bosenge et al [24] in Kisangani, who reported that 67% of infertile couples had secondary infertility and 33% primary infertility. These ndings are consistent with those from other Sub-Saharan African countries [16, 21,26,33].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Among women experiencing infertility, 78.78% had secondary infertility, while 21.22% had primary infertility. The results of this study are in agreement with those of Bosenge et al [24] in Kisangani, who reported that 67% of infertile couples had secondary infertility and 33% primary infertility. These ndings are consistent with those from other Sub-Saharan African countries [16, 21,26,33].…”
Section: Discussionsupporting
confidence: 93%
“…However, the uterine and tubal factors were not found to be associated with any type of infertility. In a similar study, Bosenge-Nguma et al [24] found ovarian factors among 35.2% of patients, uterine factors among 31.5% of patients and tubal factors among 46.3% of patients. In previous studies, Nguma et al [25] in Kisangani and Kalume et al [26] in Goma found that 67.6% and 73.31% of infertile women had globally a tubal issue, respectively.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations